Hubungan Kualitas Tidur dengan Kejadian Migrain pada Mahasiswa Fakultas kedokteran Universitas Lampung - Diaru Fauzan Farizy; Risti Graharti (Medula, 2021)
Migraine is one of the most common types of primary headache in the general population. Previous research has shown that poor sleep quality is very common among migraine sufferers and is associated with exacerbations of migraine symptoms. Information regarding the prevalence and clinical implications of poor sleep quality among individuals with migraine is also scarce. The purpose of this study was to determine the relationship between sleep quality and the incidence of migraine in medical students at the University of Lampung. This study used a cross sectional method using a questionnaire that was used to conduct a sleep and migraine survey at the Faculty of Medicine, University of Lampung. Participants with a Sleep Quality Index (Pittsburgh Sleep Quality Index) PSQI > 5 were considered to have poor sleep quality and for migraine were conducted with a questionnaire adapted by HO K-H & Ong BK-C from the International Headache Society (IHS) classification. The results of the study of 65 participants, in the univariate analysis found 13 (20%) had migraines and 36 (55%) had poor sleep quality. In the bivariate analysis, it was found that p value = 0.04 with the number of respondents experiencing poor sleep quality and migraine, there were 11 (30.6%) respondents from 36 respondents who experienced poor sleep quality. Conclusions: Poor sleep quality was prevalent among participants with migraine. It is associated with exacerbation of migraine symptoms. The results of this study indicate that there is a significant relationship between sleep quality and the incidence of migraine in students of the Faculty of Medicine, University of Lampung.